Ring 20 chromosome in a child with seizures, minor anomalies, and retardation. Issue 6 (June 1979) - Stewart, J M; Cavanagh, N; Hughes, D T
Abstract : A patient is reported with seizures, developmental delay, and minor physical anomalies. Karyotype showed a ring formation of chromosome number 20. Previously reported patients with this chromosomal aberration have typically had seizures and behavioural disorders with considerable variation in the degree of physical abnormality and mental retardation. A correct diagnosis in such a case is important for accurate genetic counselling.